2018
DOI: 10.1002/adma.201806312
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Fe Dispersed on N‐Doped Carbon Hollow Nanospheres for High‐Efficiency Electrocatalytic Oxygen Reduction

Abstract: Exploration of high‐efficiency, economical, and ultrastable electrocatalysts for the oxygen reduction reaction (ORR) to substitute precious Pt is of great significance in electrochemical energy conversion devices. Single‐atom catalysts (SACs) have sparked tremendous interest for their maximum atom‐utilization efficiency and fascinating properties. Therefore, the development of effective synthetic methodology toward SACs becomes highly imperative yet still remains greatly challenging. Herein, a reliable SiO2‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
262
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 487 publications
(287 citation statements)
references
References 58 publications
7
262
0
1
Order By: Relevance
“…Ar easonable request for more (> 37.5 %) pyridinic and metallic Ni nt he Ne lement was proposed since these components have long been recognized to play important roles in constructing M-N x sites. [40] From the consensus reached by our decision tree with previous works in this field, AI has proven to be trustworthy as ar esearch consultant. Moreover,t he decision tree identified one unique determination.…”
Section: Them Ass Ratio Between the Ionomer Nafion And Thementioning
confidence: 69%
“…Ar easonable request for more (> 37.5 %) pyridinic and metallic Ni nt he Ne lement was proposed since these components have long been recognized to play important roles in constructing M-N x sites. [40] From the consensus reached by our decision tree with previous works in this field, AI has proven to be trustworthy as ar esearch consultant. Moreover,t he decision tree identified one unique determination.…”
Section: Them Ass Ratio Between the Ionomer Nafion And Thementioning
confidence: 69%
“…It has been reported that N species play a crucial role in the electrocatalytic process, [43][44][45][46][47] with graphitic N working as an efficient active sites. [48][49][50][51] Hence, XPS was used to investigate the elemental compositions of Pt x Fe/C/N-GC-600, Pt x Fe/C/N-GC-700 and Pt x Fe/C/N-GC-800. The high-resolution N 1 s spectra of these three samples (see Fig.…”
Section: Catalyst Activity and Stability In The Mormentioning
confidence: 99%
“…During recent years, single-atom catalysis has become one of the most attractive new frontiers in catalysis as a model bridging homogeneous and heterogeneous catalysis [1][2][3][4][5][6][7]. With the aid of recent advances in synthetic methodologies, atomic-resolution characterization techniques and theoretical modelling, various single-atom catalysts (SACs) were produced and studied for catalysis [8][9][10][11][12][13][14][15][16][17][18][19][20]. Compared with clusters and nanocatalysts, SACs usually exhibit superior activity and excellent selectivity in a wide variety of catalytic reactions owing to their maximum atom efficiency, unsaturated coordinate environment and particular electronic structures [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%